Efficiency and market power in Latin American banking - Williams, Jonathan (Journal of Financial Stability, 2012)
I examine the relationship between bank efficiency and market power to test the quiet life hypothesis for a sample of 419 Latin American commercial banks between 1985 and 2010. A two-stage least squares model with instrumental variables controls for the simultaneous relationship between efficiency and market power. Citing developments in efficiency modelling, efficiencies are drawn from the random parameters stochastic frontier function model that treats unobserved heterogeneity, whilst conventional Lerner indices and the efficiency adjusted Lerner index proxy market power. The quiet life hypothesis is firmly rejected after various robustness checks. To test if bank restructuring and governance changes affect efficiency and market power, I use a difference-in-differences approach to determine the impact of bank privatisation and foreign acquisition of local banks on efficiency and market power. Privatisation is preferred over foreign acquisition though its impact is concentrated on efficiency rather than market power. The evidence suggests that bank restructuring has promoted competition at the expense of market power and yielded efficiency gains at banks under conditions of monopolistic competition.